Development of the system for multichannel microwave plasma probing in the torsatron U-2M - Berezhnyj, V.L.; Ocheretenko, V.L.; Pinos, I.B.; Skibenko, A.I.; Prokopenko, A.V.; Larin, Yu.V.; Maznichenko, S.M.; Sitnikov, D.A.; Tarasov, M.I. (Вопросы атомной науки и техники, 2009)
To study successfully the conditions for production and heating of the plasma, its dynamics in the process of an RF
discharge in the torsatron U-2M, a multichannel system for microwave diagnostics is suggested. To obtain the electron
density profiles with an asymmetric plasma cross-section in the l=2 torsatron, 5 fan channels and 3 longitudinal
channels will be used. For these measurements a quadrature interferometer at a frequency of 140 GHz is under
development. Для успішного вивчення умов створення і нагріву плазми, її динаміки в процесі ВЧ-розряду в торсатроні
У-2М створюється багатоканальна система мікрохвильової діагностики. Для одержання профілів густини
електронів з невісесиметричним перерізом плазми в двозаходному торсатроні буде використано п'ять віяльних і
три подовжніх канали. Для цих вимірювань розробляється квадратурний інтерферометр на частоті 140 ГГц з
гетеродинною індикацією фази. Для успешного изучения условий создания и нагрева плазмы, ее динамики в процессе ВЧ-разряда в
торсатроне У-2М создается многоканальная система микроволновой диагностики. Для получения профилей
плотности электронов с неосесимметричным сечением плазмы в двухзаходном торсатроне будет использовано
пять веерных и три продольных канала. Для этих измерений разрабатывается квадратурный интерферометр на
частоте 140 ГГц с гетеродинной индикацией фазы.